Can chlorhexidine gluconate baths reduce fungal colonisation in intensive care unit patients? - Teresa Nascimento; João Inácio; Daniela Guerreiro; Patrícia Patrício; Luís Proença; Cristina Toscano; Priscila Diaz; Helena Barroso (Antimicrobial Resistance and Infection Control)
Abstract Background Chlorhexidine Gluconate (CHG) bathing is widely used in Intensive Care Units (ICUs) to reduce bacterial colonisation, yet its efficacy against fungal skin colonisation, particularly Candida spp., is not well understood. This study aimed to evaluate the impact of daily CHG bathing on Candida colonisation among ICU patients. Methods From 2020 to 2022, axillary/inguinal swabs were collected from 675 ICU patients across three units on admission (Day 1, D1), Day 5 (D5) and Day 8 (D8). Patients received daily CHG bathing (either 2% impregnated wipes or 4% liquid solution) from D1 to D5, followed by soap-and-water bathing from Day 6 to D8. Standard and molecular microbiological methods were used to identify fungal species, and colony-forming units (CFUs) were quantified. Colonisation rates and fungal burden were compared across time points and bathing protocols. Results A total of 988 swabs from 675 patients were collected, 675 on D1, 203 on D5 and 110 on D8. CHG bathing had no significant impact on Candida burden at individual time points, (D1, p = 0.223; D5, p = 0.939 and D8, p = 0.669). No significant differences in colonisation or fungal burden were observed between the use of 4% CHG solution and 2% CHG-impregnated wipes upon ICU admission. However, in the subgroup of 89 patients monitored longitudinally, a transient reduction in colonisation was observed during the CHG bathing period (D1–D5), followed by a significant increase during the soap-and-water period (D6–D8) (p = 0.005; between periods: p < 0.001). Among the 329 positive swabs, 274 yielded > 100 CFU/ml. High colony counts of C. albicans (> 1000 CFU/mL) were observed, with no significant association between colonisation levels and specific Candida species (p = 0.940). Conclusions CHG bathing demonstrated only a limited and transient impact on Candida colonisation in ICU patients. Colonisation rates rebounded after cessation of CHG use, suggesting ongoing acquisition during ICU stay. These findings highlight the need for additional or alternative infection control measures targeting fungal pathogens in critical care settings.